STRATEGI DAN KUNCI SUKSES KARIR SEORANG PEMIMPIN POLITIK. - Nurhayati, Immas (KHAZANAH, 2006)
The leadership already exists thousand years ago, Research of leadership assumed that situation showed the important part in the effectiveness leadership. That’s why that to be effective, leaders should have a different way in the different condition. The next research assumed that a leader was the important part to create the effectiveness for both of attitude and environment. Early of 1980, leadership perspective aimed to strategic leadership that emphasize to the vision, motivation, and control through the values in the culture that can be adopted. The leaders useful for their organization and also for theirfollowers. A lot of leaders instead dissolve their organization. In this research, writer wants to know more about the common basic of political leadership and the strategy and the success keys in the career of political leadership. Writer will visit and do some interview with political leadership to find out more information that in line with research topics. Researching will be held on April – May 2006. Based on the analysis and explanations, we can conclude that A responsible political leadership must have a broad horizon he must have an ambition that is a determination to carry out something to reach the goal. The important thing to develop a successful leadership is the ability to create positive and conducive circumstances in the organization. It will endorse the followers to discover theirpotency, improving initiative and creative thing in them, and encourage them to move forward, consistency, protecting and keeping good name of institution. Key success of leader’s career in politic is the endorsement of elements of responsible political leadership which are inherent with in him. The elements are legitimacy, justice, integrity, visionary, role model, succession, fairness firm attitude in giving reward and punishment to the followers.